Hepcidin detects iron deficiency in Sri Lankan adolescents with a high burden of hemoglobinopathy: A diagnostic test accuracy study - Wray, K; Allen, A; Evans, E; Fisher, C; Premawardhena, A; Perera, L; Rodrigo, R; Goonathilaka, G; Ramees, L; Webster, C; Armitage, A; Prentice, A; et al. (Wiley, 2017)
Anemia affects over 800 million women and children globally. Measurement of hepcidin as an index of iron status shows promise, but its diagnostic performance where hemoglobinopathies are prevalent is unclear. We evaluated the performance of hepcidin as a diagnostic test of iron deficiency in adolescents across Sri Lanka. We selected 2273 samples from a nationally representative cross-sectional study of 7526 secondary schoolchildren across Sri Lanka and analyzed associations between hepcidin and participant characteristics, iron indices, inflammatory markers, and hemoglobinopathy states. We evaluated the diagnostic accuracy of hepcidin as a test for iron deficiency with estimation of the AUC(ROC) , sensitivity/specificity at each hepcidin cutoff, and calculation of the Youden Index to find the optimal threshold. Hepcidin was associated with ferritin, sTfR, and hemoglobin. The AUC(ROC) for hepcidin as a test of iron deficiency was 0.78; hepcidin outperformed Hb and sTfR. The Youden index-predicted cutoff to detect iron deficiency (3.2 ng/mL) was similar to thresholds previously identified to predict iron utilization and identify deficiency in African populations. Neither age, sex, nor α- or β-thalassemia trait affected diagnostic properties of hepcidin. Hepcidin pre-screening would prevent most iron-replete thalassemia carriers from receiving iron whilst still ensuring most iron deficient children were supplemented. Our data indicate that the physiological relationship between hepcidin and iron status transcends specific populations. Measurement of hepcidin in individuals or populations could establish the need for iron interventions. Am. J. Hematol. 92:196-203, 2017. © 2016 Wiley Periodicals, Inc.